2000
DOI: 10.1038/sj.bjp.0703343
|View full text |Cite
|
Sign up to set email alerts
|

Substance P mediates inflammatory oedema in acute pancreatitis via activation of the neurokinin‐1 receptor in rats and mice

Abstract: 1 Pancreatic oedema occurs early in the development of acute pancreatitis, and the overall extent of¯uid loss correlates with disease severity. The tachykinin substance P (SP) is released from sensory nerves, binds to the neurokinin-1 receptor (NK1-R) on endothelial cells and induces plasma extravasation, oedema, and neutrophil in®ltration, a process termed neurogenic in¯ammation. We sought to determine the importance of neurogenic mechanisms in acute pancreatitis. 2 Pancreatic plasma extravasation was measure… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
75
0
1

Year Published

2004
2004
2018
2018

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 98 publications
(79 citation statements)
references
References 20 publications
3
75
0
1
Order By: Relevance
“…Based on the pathological changes such as intestinal mucosa injury and mucosa exuviation, it is presumed that the linkage between cell and cell or cell and matrix of the intestinal epithelium as well as the recovery of the intestinal epithelial layer were affected by a decrease of CD44 expression after SAP, while the role of growth hormone (GH) in maintaining the integrity of epithelial structures and immune functions of the intestinal mucosa might be related to the increase of CD44 mRNA expression. P substance and its receptor such as neurokinin-1 receptor (NK-1R) and neurokinin-2 receptor (NK-2R) have played important roles in the onset and progression of AP Grady et al, 2000). The action of neurokinin has been disturbed and the intestinal mucosa injury has been aggravated due to the significant increase of expressions of NK-1R and NK-2R in the colon during SAP (Zheng et al, 2002).…”
Section: Influence Of Enteral Nutrition Deficiency On Injury Of Intesmentioning
confidence: 99%
See 1 more Smart Citation
“…Based on the pathological changes such as intestinal mucosa injury and mucosa exuviation, it is presumed that the linkage between cell and cell or cell and matrix of the intestinal epithelium as well as the recovery of the intestinal epithelial layer were affected by a decrease of CD44 expression after SAP, while the role of growth hormone (GH) in maintaining the integrity of epithelial structures and immune functions of the intestinal mucosa might be related to the increase of CD44 mRNA expression. P substance and its receptor such as neurokinin-1 receptor (NK-1R) and neurokinin-2 receptor (NK-2R) have played important roles in the onset and progression of AP Grady et al, 2000). The action of neurokinin has been disturbed and the intestinal mucosa injury has been aggravated due to the significant increase of expressions of NK-1R and NK-2R in the colon during SAP (Zheng et al, 2002).…”
Section: Influence Of Enteral Nutrition Deficiency On Injury Of Intesmentioning
confidence: 99%
“…The early enteral nutuition (EN) might be indispensable to the protection of intestinal mucosa barrier of rats (Al-Omran et al, 2003;Marik and Zaloga, 2004). Grady et al(2000) found that PAF played an important role in the progression of pancreatitis complicated with functional disturbance of intestinal mucosa barrier. Its antagonist might be a potential therapy.…”
Section: Influence Of Enteral Nutrition Deficiency On Injury Of Intesmentioning
confidence: 99%
“…Previous data (2) show that SP levels and NK-1 receptors in pancreatic acinar cells are upregulated during experimental pancreatitis in mice. In addition, NK-1 receptor deletion or antagonism protects mice against pancreatitis (3,9,15). SP-induced activation of the NK-1 receptor is an important proinflammatory step also in rat acute pancreatitis.…”
mentioning
confidence: 99%
“…The present study demonstrates that NEP is protective against the damaging effects of caerulein-induced AP by modulating physiological SP levels. Pancreatic edema, increased plasma amylase activity, and infiltration of neutrophils into the inflamed tissue are well-known characteristics of caerulein-induced AP (7,27,33,39). In AP, plasma amylase level is markedly increased due to this enzyme escaping into the blood from damaged pancreatic tissues (40).…”
Section: Discussionmentioning
confidence: 99%
“…SP-NK1R interaction plays an early and important role in the inflammatory cascade and promotes excessive activation of inflammatory cells. Proinflammatory mechanisms of SP are thought to be its effects on plasma extravasation, neutrophil recruitment, and inflammatory mediator synthesis upon exogenous stimuli (7,8). SP is encoded by the preprotachykinin-A (PPTA) gene, produced primarily by sensory nociceptive neurons, but it can also be produced by inflammatory cells and pancreatic acinar cells (9)(10)(11).…”
mentioning
confidence: 99%